STUDI GEOMORFOLOGI DAERAH TENILO DAN SEKITARNYA, KECAMATAN TILAMUTA, KABUPATEN BOALEMO, PROVINSI GORONTALO - Yenayo, Hafipa; Arifin, Yayu Indriati; Hutagalung, Ronal (UNM Geographic Journal, 2024)
The research area is located in the village of Tenilo and its surroundings, which exhibit interesting land characteristics and features, making it an attractive site for study. This research aims to analyze and map the geomorphological conditions in order to obtain information related to various geomorphological aspects. The method used is the analysis of geomorphological aspects. The results of this study indicate that the geomorphological units in the area include volcanic hills, denudational hills, and marine plains. The geomorphological aspects of this area are categorized as follows: morphography, consisting of hill and plain units; morphometry, with elevation points ranging from 0 to 350 meters above sea level, and slope gradients from flat to steep; morphogenesis, which includes active morphostructures such as faults and joints, and passive morphostructures such as andesite, volcanic breccia, and alluvial deposits; morphodynamics, characterized by river flow patterns including dendritic and sub-parallel patterns, with river stages ranging from mature to youthful. According to the regional geological map of the Tilamuta sheet, the morphochronology of the research area dates back to the Eocene to Holocene epochs, and the morpho-arrangement of the area is dominated by high erosion processes.